Bounded Rationality and Policy Diffusion: Social Sector Reform in Latin America - Finkel, Alvin (Labour / Le Travail, 2008)
The article reviews the book, "Bounded Rationality and Policy Diffusion: Social Sector Reform in Latin America," by Kurt Weyland.
Keywords: BOOKS -- Reviews; BOUNDED Rationality & Policy Diffusion: Social Sector Reform in Latin America (Book); Nonfiction; Social policy; WEYLAND, Kurt